Rancang Bangun Website Sebagai Sarana Promosi Usaha Madu Kele-Kele di Desa Bongkasa Pertiwi - Ni Made Desni Dwi Arisaputri; Gst. Ayu Vida Mastrika Giri (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2025)
Kele-Kele Honey from Bongkasa Pertiwi Village is a superior product with large market potential but is still little known by the wider community. This research aims to develop a website as an effective promotional tool to increase awareness and sales of Kele-Kele honey. By implementing a Rapid Application Development (RAD) approach, website development is carried out quickly and iteratively, enabling active involvement of business owners in the development process and feature adjustments based on user feedback. The research results show that the website developed has succeeded in increasing public awareness about Kele-Kele honey and supporting the growth of local businesses. The practical implication of this research suggests that employing Rapid Application Development (RAD) in web development could be an effective strategy to enhance the sales and visibility of local products such as Kele-Kele honey. To further promote the growth of small and medium-sized enterprises, future studies could focus on developing new features and conducting a more comprehensive evaluation of the effectiveness of online promotions.